BRIDGING POLICY AND PRACTICE: DESIGNING INCLUSIVE, LANGUAGE-SENSITIVE EDUCATION SYSTEMS IN POST-WAR RECOVERY - Maksymets, Kateryna; Maksymets, Olena (Forestry Education and Science: Current Challenges and Development Prospects, 2026)
This paper examines the integration of inclusive pedagogy and applied linguistics to rebuild post-war education systems, with a specific focus on English Language Teaching. To actively advance Quality Education (SDG 4), we advocate for language-sensitive, trauma-informed frameworks, such as Universal Design for Learning, to ensure equal access and psychological safety. Sustainable recovery requires embedding these approaches into public policy, curricula, and continuous teacher training. By bridging the gap between macro-level policy and micro-level classroom practice through international cooperation, we can construct resilient educational ecosystems that promote social inclusion, combat disparities (SDG 10), and foster enduring peace and strong institutions (SDG 16)